ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Nurul Hidayati, 10.05.52.0118; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2014)
This study aims to determine the effect of ROI, EPS, DER, SIZE , and CR on stock prices of mining companies listed on the Indonesia Stock Exchange ( IDX ). The population is the entire mining companies in Indonesia Stock Exchange ( IDX ) the number of 66 companies and research over the period 2009 to 2011 . Samples taken in this study is as much 22perusahaan . The sampling technique used was purposive sampling . The analytical tool used in this study is Multiple Linear Regression Analysis. The results showed that the coefficient of determination in this study is the value of Adjusted R Square of 82.2 % . As for the statistical test of the F - test shows that, between ROI, EPS, DER, SIZE, and CR simultaneously affect the stock price . And partial hypothesis testing results show that there is a significant positive effect between ROI , EPS , and the SIZE of the stock price . As for DER, and CR positive effect was not significant. Keywords: Return On Investment, Earning Per Share, Debt To Equity Ratio, size, Current ratio end Stock Price